Isaac on Jewish and Christian altars : polemic and exegesis in Rashi and the Glossa ordinaria - Schoenfeld, Devorah (Fordham series in medieval studies., 2013)
"Devorah Schoenfeld's new work offers an in-depth examination of two of the most influential Christian and Jewish Bible commentaries of the High Middle Ages. The Glossa Ordinaria and Rashi's commentary were standard texts for Bible study in the High Middle Ages, and Rashi's influence continues to the present day. Although Rashi's commentary and the Glossa developed at the same time with no known contact between them, they shared a way of reading text that shaped their interpretations of the central religious narrative of the Binding of Isaac. Schoenfeld's text examines each commentary unto itself and offers a detailed comparison, one that illustrates the similarities between Rashi and the Gloss that derive not merely from their shared late antique heritage but also from their common twelfth-century context, and the Jewish-Christian polemic in which they both, implicitly or explicitly, take part."--Project Muse